2013
DOI: 10.1007/s11999-012-2615-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Engineering of Juvenile Human Chondrocytes Improves Scaffold-free Mosaic Neocartilage Grafts

Abstract: Genetic augmentation of jCh and creation of mosaic neocartilage may improve graft viability and articular healing compared with naïve neocartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Alternatively, initial high BMP2 expression and release from fMSCs could have caused a transient increase in number of osteoclasts derived from hematopoietic stem cells [24] but there was no evidence of bone remodeling in our histology to suggest this mechanism was at work. Based on our in vitro findings with fMSC, and recent work from our laboratory demonstrating superior outcomes of neocartilage growth with a mosaic of 90% naïve and 10% Ad-BMP2-transduced juvenile chondrocytes [25] , it was anticipated that the dilution of BMP2 expressing cells in the rapidly proliferating fMSC population may be an advantage in vivo. In addition, Brady and colleagues recently demonstrated that recombinant BMP2 can induce chondrogenesis in pellet culture of fetal but not adult MSCs [23] .…”
Section: Discussionmentioning
confidence: 92%
“…Alternatively, initial high BMP2 expression and release from fMSCs could have caused a transient increase in number of osteoclasts derived from hematopoietic stem cells [24] but there was no evidence of bone remodeling in our histology to suggest this mechanism was at work. Based on our in vitro findings with fMSC, and recent work from our laboratory demonstrating superior outcomes of neocartilage growth with a mosaic of 90% naïve and 10% Ad-BMP2-transduced juvenile chondrocytes [25] , it was anticipated that the dilution of BMP2 expressing cells in the rapidly proliferating fMSC population may be an advantage in vivo. In addition, Brady and colleagues recently demonstrated that recombinant BMP2 can induce chondrogenesis in pellet culture of fetal but not adult MSCs [23] .…”
Section: Discussionmentioning
confidence: 92%
“…As a next step, to distinguish between spontaneous and focused regeneration, load‐bearing regions of the knee such as the medial and femoral condyle will be explored in rodents and other animal models. The trochlear groove in a lower weight‐bearing region is considered an appropriate model for proof of concept studies . Earlier studies that employed biomaterials on rat trochlear groove regeneration for critical sized defects have shown similar rates of regeneration .…”
Section: Discussionmentioning
confidence: 99%
“…Using our experience with the nude rodent model to study knee cartilage healing [ 25 , 26 ] we determined the healing potential of the sConstructs. The time point of healing, 5 weeks, was selected such that we could detect either a delay or acceleration of repair among our comparison groups.…”
Section: Introductionmentioning
confidence: 99%